RETRACTED: Short-term responses of Spinach (Spinacia oleracea L.) to the individual and combinatorial effects of Nitrogen, Phosphorus and Potassium and silicon in the soil contaminated by boron - Ma, Jing; Ali, Sajjad; Saleem, Muhammad Hamzah; Mumtaz, Sahar; Yasin, Ghulam; Ali, Baber; Al-Ghamdi, Abdullah Ahmed; Elshikh, Mohamed S.; Vodnar, Dan C.; Marc, Romina Alina; Rehman, Abdur; Khan, Muhammad Nauman; et al. (Frontiers in Plant Science, 2022)
While of lesser prevalence than boron (B) deficient soils, B-rich soils are important to study as they can cause B toxicity in the field and subsequently decrease crop yields in different regions of the world. We have conducted the present study to examine the role of the individual or combined application of silicon (Si) and NPK fertilizer in B-stressed spinach plants (Spinacia oleracea L.). S. oleracea seedlings were subjected to different NPK fertilizers, namely, low NPK (30 kg ha–2) and normal NPK (60 kg ha–2)], which were also supplemented by Si (3 mmol L–1), for varying levels of B in the soil i.e., 0, 250, and 500 mg kg–1. Our results illustrated that the increasing levels of B in the soil caused a substantial decrease in the plant height, number of leaves, number of stems, leaf area, plant fresh weight, plant dry weight, chlorophyll a, chlorophyll b, total chlorophyll, carotenoid content, net photosynthesis, stomatal conductance, transpiration rate, magnesium content in the roots, magnesium contents in the shoots, phosphorus content in the roots, phosphorus content in the leaves in the shoots, iron content in the roots, iron content in the shoots, calcium content in the roots, and calcium content in the shoots. However, B toxicity in the soil increased the concentration of malondialdehyde, hydrogen peroxide, and electrolyte leakage which were also manifested by the increasing activities of enzymatic [superoxidase dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX)], and non-enzymatic antioxidants (phenolic, flavonoid, ascorbic acid, and anthocyanin content). B toxicity in the soil further increased the concentration of organic acids in the roots such as oxalic acid, malic acid, formic acid, citric acid, acetic acid, and fumaric acid. The addition of Si and fertilizer levels in the soil significantly alleviated B toxicity effects on S. oleracea by improving photosynthetic capacity and ultimately plant growth. The increased activity of antioxidant enzymes in Si and NPK-treated plants seems to play a role in capturing stress-induced reactive oxygen species, as was evident from the lower levels of oxidative stress indicators, organic acid exudation, and B concentration in the roots and shoots of Si and NPK-treated plants. Research findings, therefore, suggested that the Si and NPK application can ameliorate B toxicity in S. oleracea seedlings and result in improved plant growth and composition under metal stress as depicted by the balanced exudation of organic acids.